2022
DOI: 10.1097/sla.0000000000005562
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Virtual Professional Development Coaching Program on the Professional Fulfillment and Well-Being of Women Surgery Residents

Abstract: Objective: Evaluate the effect of a virtual coaching program offered to women surgery residents in a surgical society. Background: Randomized controlled experiments evaluating the effect of coaching on trainee well-being and burnout is lacking. Methods: Women surgery residents in the Association of Women Surgeons were recruited to participate in a randomized controlled trial of the effects of a virtual coaching program on trainee well-being. Attending surgeons served as coaches after completing in-person train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 19 publications
1
41
1
Order By: Relevance
“…The measurement of outcome domain and the missing outcome domain were found to be at some risk of bias for the Dyrbye et al [ 19 ] and McGonagle et al [ 35 ] RCTs, respectively. The Palamara et al study [ 40 ] was found to have some concerns of bias for the deviations from intended interventions domain and the missing outcome domain. The included non-randomized interventional studies and quantitative portions of the mixed-methods studies were mostly at moderate or serious risk of bias across all domains ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of outcome domain and the missing outcome domain were found to be at some risk of bias for the Dyrbye et al [ 19 ] and McGonagle et al [ 35 ] RCTs, respectively. The Palamara et al study [ 40 ] was found to have some concerns of bias for the deviations from intended interventions domain and the missing outcome domain. The included non-randomized interventional studies and quantitative portions of the mixed-methods studies were mostly at moderate or serious risk of bias across all domains ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In their 2022 study, Dyrbye et al [ 31 ] reported a 2.5% decrease in burnout in the intervention group, whereas burnout increased in the control group (p = 0.007). Palamara et al [ 40 ] reported a decrease in burnout score from 1.39 to 1.19 for participants who received coaching (p = 0.026). The remaining studies either did not assess these outcomes or reported no difference ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Consultations or coaching, as a professional continuous service, might play an important role in transmitting health information and providing decision support 56 . Palamara and colleagues 57 reported an improvement in well-being among female surgery residents who received vital coaching over a web-based video platform. Nonetheless, Sieczkowska et al 58 revealed the available evidence is not of sufficient quality to support the use of self-reported health coaching as a health care intervention for weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Post-program there was improvement in depression and emotional exhaustion. A more wide-scale example of an EI related initiative is the randomized control trial (RCT) conducted nationally examining the impact of a virtual Professional Development Coaching Program on 237 women surgery resident participants [51]. Coaching has been shown to promote reflection while strengthening awareness and motivation.…”
Section: Emotional Intelligencementioning
confidence: 99%